Integrated continuous winemaking process involving sequential alcoholic and malolactic fermentations with immobilized cells - Genisheva, Zlatina Asenova (2014)
An integrated winemaking process – including sequential alcoholic and malolactic fermentations operated continuously – was developed. For the continuous alcoholic fermentation, yeast cells (Saccharomyces cerevisiae) were immobilized either on grape stems or on grape skins, while bacterial cells (Oenococcus oeni) used for conducting continuous malolactic fermentation were immobilized on grape skins only. The produced wines were subjected to chemical analysis by HPLC (ethanol, glycerol, sugars and organic acids) and by gas chromatography (major and minor volatile compounds). The final proposed integrated continuous process permitted the production of 960 mL/d of a dry white wine, with an alcoholic strength of about 13 vol%, by using two 1.5 L tower bed reactors packed with 260 g of grape skins. The produced wines revealed a good physicochemical quality. Moreover, 67% of the malic acid concentration could be reduced in the second reactor. Both fermentative processes proved to be much more efficient than those conducted traditionally with free cells or even with immobilized cells, but in the batch mode of operation.